PENENTUAN RUKYAT HILAL 1446 H KEMENAG DAN MAHASISWA DI WILAYAH LUBUKLINGGAU - Sa'datul Ashfiya; Rosa Sandini; Neza Pirna; Zulkifli (Syariah: Jurnal Hukum Keluarga Islam, 2025)
This research examines an empirical study of the participation of the Ministry of Religious Affairs (Kemenag) of Lubuklinggau City and students of Universitas Islam Nusantara (UIN) Al-Azhaar Lubuklinggau in the rukyat hilal (crescent moon observation) determination for the year 1446 Hijri. Focusing on the dynamics of collaboration, differences, and commonalities between the two parties, this study aims to describe in detail the procedures and respective roles in the execution of hilal observation. Utilizing a descriptive qualitative approach, data was collected through direct observation at strategic rukyat locations like Bukit Sulap, in-depth interviews with representatives from Kemenag and UIN faculty/students, and the study of official documentation. The research findings indicate that Kemenag Lubuklinggau City carries out rukyat procedures in accordance with official mandates and national guidelines, using standard equipment and reporting its results for the Sidang Isbat (official crescent moon sighting deliberation). Students of UIN Al-Azhaar Lubuklinggau participate as an integral part of academic practice and the regeneration process for falak (Islamic astronomy) experts, with a focus on empirical learning and the application of theory in the field. Further analysis reveals a positive synergy between Kemenag and the students, where Kemenag provides practical guidance and the students bring an academic enthusiasm. Although there are differences in official mandates, equipment completeness, and experience levels, both parties are united by the same spiritual goal to accurately determine the beginning of the Hijri month. This collaboration not only strengthens the validity of rukyat results at the local level but also contributes to the development of falak science and the nurturing of future Islamic astronomy experts in Lubuklinggau.